2005
DOI: 10.1002/ejoc.200500103
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Stereochemical Assignment and Fluorescence Tuning of the Small Molecule Tool, (–)‐Blebbistatin

Abstract: (–)‐Blebbistatin (1), a recently discovered small molecule inhibitor of the ATPase activity of non‐muscle myosin II has been prepared from methyl 5‐methylanthranilate (6) in three steps. This flexible synthetic route has also been used to prepare a nitro group‐containing analogue 12 that has modified fluorescence properties and improved stability under microscope illumination. The key step in the synthesis of 1 and its analogues was the asymmetric hydroxylation of the quinolone intermediate 3 using the Davis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 25 publications
(26 reference statements)
3
65
0
Order By: Relevance
“…† An interesting variation in the degree of asymmetric induction in the quinolone hydroxylation reaction was also observed as a function of structure, although in all cases the absolute configuration of the resulting analogue was the same [(S)-(-)]. Quinolones 15-17 all reacted with (-)-[ (8,8-dichlorocamphoryl)sulfonyl]oxaziridine (18) 11 under optimised conditions to give the desired analogues 5-7 respectively in good yield and high enantiomeric excess (ee 86-90%) in line with our report 9 on the synthesis of 1 (Scheme 1, column 8). As expected, 9 the ee of the asymmetric hydroxylation reaction for these substrates was reduced significantly when the dihydro-oxaziridine 19 was used instead of 18 (Scheme 1, column 9).…”
Section: (S)-(-)-blebbistatin (1) Analogue Synthesissupporting
confidence: 82%
See 3 more Smart Citations
“…† An interesting variation in the degree of asymmetric induction in the quinolone hydroxylation reaction was also observed as a function of structure, although in all cases the absolute configuration of the resulting analogue was the same [(S)-(-)]. Quinolones 15-17 all reacted with (-)-[ (8,8-dichlorocamphoryl)sulfonyl]oxaziridine (18) 11 under optimised conditions to give the desired analogues 5-7 respectively in good yield and high enantiomeric excess (ee 86-90%) in line with our report 9 on the synthesis of 1 (Scheme 1, column 8). As expected, 9 the ee of the asymmetric hydroxylation reaction for these substrates was reduced significantly when the dihydro-oxaziridine 19 was used instead of 18 (Scheme 1, column 9).…”
Section: (S)-(-)-blebbistatin (1) Analogue Synthesissupporting
confidence: 82%
“…Quinolones 15-17 all reacted with (-)-[ (8,8-dichlorocamphoryl)sulfonyl]oxaziridine (18) 11 under optimised conditions to give the desired analogues 5-7 respectively in good yield and high enantiomeric excess (ee 86-90%) in line with our report 9 on the synthesis of 1 (Scheme 1, column 8). As expected, 9 the ee of the asymmetric hydroxylation reaction for these substrates was reduced significantly when the dihydro-oxaziridine 19 was used instead of 18 (Scheme 1, column 9). Bach et al 12 have reported a detailed computational analysis of the transition state involved in lithium enolate hydroxylation reactions using an oxaziridine.…”
Section: (S)-(-)-blebbistatin (1) Analogue Synthesissupporting
confidence: 76%
See 2 more Smart Citations
“…The drug exhibits stereo specificity, with the (−) isoform being the active compound as determined by in vitro motility assay and by its ability to prevent cell division [27,32].…”
Section: Introductionmentioning
confidence: 99%